Safety, Tolerability and efficacy of Rapid Optimization, helped by NT‐proBNP and GDF‐15, of Heart Failure therapies (STRONG‐HF): rationale and design for a multicentre, randomized, parallel‐group study. (19th August 2019) - Kimmoun, Antoine; Cotter, Gad; Davison, Beth; Takagi, Koji; Addad, Faouzi; Celutkiene, Jelena; Chioncel, Ovidiu; Solal, Alain Cohen; Diaz, Rafael; Damasceno, Albertino; Duengen, Hans‐Dirk; Filippatos, Gerasimos; et al.
Abstract : Aims: Patients admitted for acute heart failure (HF) are at high risk of readmission and death, especially in the 90 days following discharge. We aimed to assess the safety and efficacy of early optimization of oral HF therapy with beta‐blockers (BB), angiotensin‐converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB) or angiotensin receptor–neprilysin inhibitors (ARNi), and mineralocorticoid receptor antagonists (MRA) on 90‐day clinical outcomes in patients admitted for acute HF. Methods: In a multicentre, randomized, open‐label, parallel‐group study, a total of 900 patients will be randomized in a 1:1 ratio to either 'usual care' or 'high‐intensity care'. Patients enrolled in the usual care arm will be discharged and managed according to usual clinical practice at the site. In the high‐intensity care arm, doses of oral HF medications – including a BB, ACEi or ARB, and MRA – will be up‐titrated to 50% of recommended doses before discharge and to 100% of recommended doses within 2 weeks of discharge. Up‐titration will be delayed if the patients develop worsening symptoms and signs of congestion, hyperkalaemia, hypotension, bradycardia, worsening of renal function or significant increase in N‐terminal pro‐B‐type natriuretic peptide between visits. The primary endpoint is 90‐day all‐cause mortality or HF readmission. Conclusions: STRONG‐HF is the first study to assess whether rapid up‐titration of evidence‐based guideline‐recommended therapies with close follow‐up in a large cohort of patients discharged from an acute HF admission is safe and can affect adverse outcomes during the first 90 days after discharge. Clinical Trial Registration: ClinicalTrials.gov Identifier NCT03412201.